2015
DOI: 10.1128/jb.02149-14
|View full text |Cite
|
Sign up to set email alerts
|

Photoheterotrophic Fluxome in Synechocystis sp. Strain PCC 6803 and Its Implications for Cyanobacterial Bioenergetics

Abstract: This study investigated metabolic responses in Synechocystis sp. strain PCC 6803 to photosynthetic impairment. We used 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU; a photosystem II inhibitor) to block O 2 evolution and ATP/NADPH generation by linear electron flow. Based on 13 C-metabolic flux analysis ( 13 C-MFA) and RNA sequencing, we have found that Synechocystis sp. PCC 6803 employs a unique photoheterotrophic metabolism. First, glucose catabolism forms a cyclic route that includes the oxidative pentose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…S6), showing its transcription under the dark condition. A previous study also revealed that RuBisCO can fix CO 2 without a fully functional Calvin cycle, as might be found in the dark condition (You et al, ). NaH 13 CO 3 is also incorporated into aspartate and glutamate (6–8%), derivatives from the TCA cycle, through the PEP carboxylase reaction.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…S6), showing its transcription under the dark condition. A previous study also revealed that RuBisCO can fix CO 2 without a fully functional Calvin cycle, as might be found in the dark condition (You et al, ). NaH 13 CO 3 is also incorporated into aspartate and glutamate (6–8%), derivatives from the TCA cycle, through the PEP carboxylase reaction.…”
Section: Resultsmentioning
confidence: 52%
“…Numbers after condition symbol designate independent data sets. References: (D), this study; H1, (You et al, ); H2, (Nakajima et al, ); M1, (You et al, ); M2, (Nakajima et al, ); A1, (Young et al, ); and A2, (Xiong et al, ). The fluxes are shown in their absolute values in mmol/g DW/h.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, the herbicide DCMU specifically blocks the PQ binding site of PSII and interrupts the water splitting. Under such inhibitory circumstances, cyanobacteria can up-regulate both glucose oxidation (using the OPP pathway) and the CEF around PSI to compensate for the requirement of NADPH and ATP, respectively [39]. In this case, cyanobacterial RuBisCO is still functioning for CO 2 fixation.…”
Section: Cyanobacterial Photomixotrophic Metabolismmentioning
confidence: 99%
“…Oscillatoria limnetica is capa-ble of anaerobic, sulphide dependent photo-assimilation of carbon dioxide [15]. Rana et al (2014) has been reported that fresh cow dung is a good source of different cyanobacterial species [16].…”
Section: Introductionmentioning
confidence: 99%